Enhancement of Dispersion, Thermophysical and Electrical Properties of Metals (Na, Al, Li) Treated Water Based Carbon Nanofluids - Zhu, Lei; Meng, Ze-Da; Chen, Ming-Liang; Choi, Jong-Geun; Park, Chong-Yeon; Lee, Shi-Choon; Hong, Dae-Seung; Lee, Jeong-Geol; Oh, Won-Chun (Asian Journal of Chemistry, 2011)
Nanofluids have been paid attention because of the intriguing heat transfer enhancement performances as one kind of promising heat transfer media. This paper reports an experimental work on the enhancement of dispersion, thermophysical and electrokinetic properties of aqueous suspensions of metal treated carbon nanoparticles (nanofluids). In this study, a simple route used to synthesize metal (Na, Al, Li) treated carbonaceous nanomaterials was studied. The dispersion effect, electrical conductivity, thermal diffusivities of the metal-carbon-nanofluids system were introduced and discussed. The results show that these properties were significantly enhanced, which could be due to not only the outstanding physical and electrical properties of the carbon nanomaterials but also to the introduction of metal ions.